The Evaluation of Foreman Competency Suitability on Consumer Complaints - Kusumanugraha, yaffi Arrizki (Universitas Negeri Semarang, 2018)
Abstract. The construction industry is one of the most developed industries around the world. Similar to the housing construction industry, consumers who buy a house on the developers sometimes have a complaint about the units they buy. Because of the consumer complaints, the developers expend more money to use the services of foreman complaints. Quality of foreman complains determines the result of consumer complaint work. Elements of competence that affect the performance of the foreman complain were analyzed using SPSS and descriptive percentage. Descriptive method of percentage of frequency calculated in percent. The elements analyzed are the skills competence, the work experience competence, the discipline competence and the wage competency. The results of the research showed that the elements that affected the foreman complaints are the skills competence 88.56%, the work experience competence 85.56%, the skills competence 88.56% the discipline competence 89.07% and the wage competency 89.73%. The strategies that must be implemented to improve the performance of the foreman complain are to supervise the continues improvement of the team owner, and also repeat orders according to the portion (the foreman capacity), selecting the workman or labor that will be used by the foreman to do a job and also make a skill assessment from the foreman and his team, conducting training programs for the foreman and the craftsman can also be a strategy to improve the performance of the foreman complain.